Assessment on Usage of YouTube, Instagram, and TikTok for Information Search among Undergraduate Students of Lagos State University (LASU), Lagos State - Dada, Kayode Sunday John (Information Research Communications, 2025)
Aim/Background This quantitative study examines the uses, gratifications, and academic impacts of YouTube, Instagram, and TikTok among 521 undergraduate students at Lagos State University (LASU). It explores platform preferences, purposes of use, motivational factors, and effects on study habits in a resource-constrained context to guide educational optimization and minimize distractions. Materials and Methods A descriptive survey design was used with stratified random sampling (n=521 from ~10,000 students). A 30-item, 5-point Likert-scale questionnaire assessed academic benefit, distraction, tasks, information access, missed deadlines, and motivations (learning, entertainment, creativity). Validated through expert review and pilot testing (Cronbach’s α=0.85), it was administered online via Google Forms, achieving a 95% response rate. Data was analyzed using descriptive statistics (means, standard deviations, frequencies) in SPSS; mean interpretation: 1.00-2.49=Low, 2.50-3.49=Moderate, 3.50-5.00=High (decision mean=3.00). Results YouTube dominated academic use (learning: M=3.95, SD=1.00; tasks: M=3.74, SD=1.04; information: M=3.85, SD=1.03; benefit: M=3.59, SD=1.18), with 60.2-75.6% agreement and minimal distraction (M=2.09, SD=0.97). Instagram (learning: M=2.90, SD=1.10; entertainment: M=3.56, SD=1.08) and TikTok (learning: M=2.68, SD=1.15; entertainment: M=3.66, SD=1.13; creativity: M=3.76, SD=1.07) were favored for entertainment and creativity but showed lower academic benefit (M=2.36/2.30) and higher distraction (M=2.64/2.63). Missed deadlines were low across platforms (M=2.09-2.33). TikTok had the highest variability (SD=1.11-1.17), indicating polarized use; YouTube showed consistent engagement (SD=0.97-1.04). Conclusion Students selectively use platforms based on needs: YouTube for learning and information with low distraction, Instagram and TikTok for entertainment and creativity with limited academic value. Negative academic impacts are minimal. Recommend integrating YouTube into curricula and addressing data access barriers to enhance equitable learning outcomes.
Keywords: Academic Performance; Instagram; Social Media; TikTok; YouTube.